Limbah Tempurung Kelapa diuji Guna Menjadi Bahan Bakar Alternatif - Arhami; Machmud, M. Nizar; Ali, Masri (Journal of Engineering and Science, 2022)
Pyrolysis is a thermo-chemical which decomposition of organic material through heating process with absent or little oxygen (anaerobic). The purposes of study are design pyrolyzer of coconut shell being to alternative fuels, knowing much of oil from pyrolysis process with method of counter flow and parallel flow, and knowing heat energy or caloric energy which was produced from pyrolysis process with method of counter flow and parallel flow in condenser. The research with through experiments the pyrolyzer which includes reactor, distribution pipe, and condenser. Research methods are the experiment of pyrolysis process at temperature 35oC during 60 minutes with condensation method, counter flow and parallel flow. Results of experiments are data of gas fuels mass obtained 42 grams which used pyrolysis process of coconut shell in the amount of 1000 gr, until produces pyrolysis oil as 198 grams (counter flow) and 196 grams (parallel flow). Counter flow method can absorb a heat as 1304,762 kJ and heat loss through gasses as 462,842 kJ, even though parallel flow no more than absorb as 1200,83 kJ and heat loss through gasses as 545,271 kJ.